Hambatan Ekspor Crude Palm Oil (CPO) Indonesia ke Uni Eropa pasca Kebijakan Renewable Energy Directive (RED) - Jevon Natashya (Jurnal Sentris, 2019)
Beside Malaysia, Indonesia is also one of the largest Crude Palm Oil (CPO) producer and exporter in the world. European Union is one of Indonesia’s trading partner and the biggest importer of CPO that used for the biofuel production, especially the biodiesel for transportation sector. But, in 2009, European Union released the Renewable Energy Directive (RED) that required all members to used renewable energy for every sector with the minimum requirement 20% for general sectors and 10% for transportation sectors. While this policy will make the European Union countries used the clean energy, RED became a new kind of NonTariff barriers for Indonesia’s CPO that become an important commodity from Indonesia. This paper will explain by the theory of International Political Economy (IPE) by focused into the Neo-Mercantilism to the analysis of Non-Tariff barriers that used by European Union for the CPO import into Indonesia. Besides that, the writer also used a National Interest concept to explain the importance of CPO for Indonesia and European Union Countries that agreed with the RED.